2010
DOI: 10.1128/jcm.01482-09
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Infection Caused by Cupriavidus gilardii in a Child with Aplastic Anemia

Abstract: Cupriavidus gilardii is a Gram-negative bacterium that has rarely been associated with human infections. We report a fatal case of sepsis caused by C. gilardii in a previously healthy 12-year-old female. CASE REPORTWhile vacationing in Europe, a previously healthy 12-yearold female was diagnosed with severe idiopathic aplastic anemia. One week after presentation, the patient was transferred to a hospital in the United States near her home. Laboratory evaluation at the time of admission was significant for a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 8 publications
4
49
0
2
Order By: Relevance
“…Three species of interest were detected within this order, Cupriavidus gilardii (4 CD patients versus 0 controls), Massilia timonae (5 CD patients versus 0 controls), and Paucimonas lemoignei (4 CD patients versus 0 controls). C. gilardii is not known for its pathogenicity; however, it has been reported to infect humans, in one case causing fatal sepsis following the dissemination of an infection with intestinal focus (33). M. timonae has also been reported to infect humans, being isolated from blood, cerebrospinal fluid, and bone samples (36).…”
Section: Resultsmentioning
confidence: 99%
“…Three species of interest were detected within this order, Cupriavidus gilardii (4 CD patients versus 0 controls), Massilia timonae (5 CD patients versus 0 controls), and Paucimonas lemoignei (4 CD patients versus 0 controls). C. gilardii is not known for its pathogenicity; however, it has been reported to infect humans, in one case causing fatal sepsis following the dissemination of an infection with intestinal focus (33). M. timonae has also been reported to infect humans, being isolated from blood, cerebrospinal fluid, and bone samples (36).…”
Section: Resultsmentioning
confidence: 99%
“…Although other Cupriavidus species such as C. pauculus, C. gilardii, and a new Cupriavidus species have been described as causes of human infections (2,7,8), to our knowledge, this is the first reported case of proven human invasive infection with C. metallidurans, a nosocomial septicemia, revealing a pathogenic potential for this bacterium. The identification is reliable only through 16S rRNA gene sequencing.…”
mentioning
confidence: 84%
“…Paracoccus yeei (Rhodobacteraceae family) has been reported as an etiologic agent of heart failure (Funke et al, 2004) while Stenotrophomonas maltophilia is an important nosocomial pathogen, especially in debilitated and immunocompromised persons (Denton and Kerr, 1998). Rhizobium massiliae has been isolated from the nasal swab of a patient with endocarditis (Greub et al, 2004) and Cupriavidus gilardii has recently been reported to be the cause of a muscular abscess in a renal transplant recipient (Tena et al, 2014) and of a fatal infection of a child with aplastic anemia (Karafin et al, 2010).…”
Section: Figmentioning
confidence: 99%